Globalization under construction : governmentality, law, and identity - Perry, Richard Warren; Maurer, Bill, 1968- (University of Minnesota Press, 2003)
The future outlines of the new global order are the constant object of speculation--economic, political, and metaphysical. From the sunny new world proclaimed by global free marketers to the rebellion against globalization unleashed in the streets of Seattle and Genoa, to the doomsdays envisioned by transnational terrorists and counterterrorists alike, this emerging global-millennial epoch is foretold alternately as redemption or apocalypse. The authors consider these sweeping descriptions of humankind's future, as well as the discourses of globalization that filter and frame them, from perspectives in anthropology, geography, law, sociology, and cultural studies. Their goal is not to resolve the ultimate semantic or philosophical question of what "globalization" really is; instead, their essays explore the forms, practices, and effects of governmentality integral to global modernity's architecture. In Globalization under Construction, the authors ask: What are the rationalities of government implicit in global modernity's project of mobilizing space, time, and difference? And what difference does it make to the globalization debates to put those rationalities in the foreground of critical analysis? Altogether, their work attempts to discern in the disparateness of contemporary events an emerging pattern of governmentality, techniques of governance and assemblages of intersecting arguments about the history of the present and the nature of the future that our present portends. A kaleidoscopic look at the intersections of globalization and governance